Understanding the influence of digital technology on adolescent mental health and violent behavior - Radoičić, Danijela (PONS - medicinski časopis, 2024)
The aim: Examine the degree and nature of digital violence among adolescents. Method: The research was carried out on a sample of adolescents with an average age of 16.07 years who attend the medical school in Ćuprija. The research process was conducted using the survey method and questionnaire technique on a sample of 109 respondents. A range of statistical tests, such as frequency analysis, reliability analysis, t test, and ANOVA test were utilized. The conclusion was reached at the 0.05 level of statistical significance. Results: A total of 11.2% of respondents experienced some form of violence on the Internet, 20.2% received disturbing content or an offensive message, 13.8% were the subject of unwanted filming and sending recorded material to others and 13.8% were harassed by phone. On the other hand, 7.3% of adolescents committed violence against others via the Internet, 9.2% sent disturbing content or an offensive message, 10.1% recorded others on the phone and sent the content to others, 4.6% disturbed others on the phone. No statistically significant differences were identified in the frequency of digital violence depending on the gender and age of adolescents. Conclusion: The use of digital technology to commit violence among adolescents is present, and the most common forms of violence are sending inaccurate and false information to friends and family members, creating and sending false information via chat, spreading rumors, as well as the use of sexual symbols in communication.Key words: digital violence, cyberbullying, adolescents, digital technology
Keywords: digital violence, cyberbullying, adolescents, digital technology